Cardiovascular safety liabilities of VEGFR-2 inhibitors - Pannucci, Patrizia (2024)
The identification of the vascular endothelial growth factor (VEGF) as a crucial determinant in neoangiogenesis, as well as the role of its overexpression in tumour growth and dissemination, have provided an attractive target for more specific cancer treatments. In particular, since the clinical approval of the first receptor tyrosine kinase inhibitor (RTKI) in 2001, several agents targeting vascular endothelial growth factor receptor (VEGFR) signalling have been approved for the treatment of a variety of malignancies. However, the improved clinical outcomes associated with these therapeutics have been accompanied by unanticipated cardiovascular toxicities, in particular hypertension, resulting in both acute- and long-term cardiovascular dysfunctions, which still represent a major cause of morbidity and mortality in cancer survivors. As a result, cardiovascular safety of VEGFR inhibitors remains a major challenge in oncology, since unanticipated and poorly controlled cardiovascular toxicities induced by these therapeutics often result in a reduction of therapeutic dosage or treatment interruption, therefore influencing cancer management. To that end, this project aimed to comprehensively characterise the cardiovascular safety liabilities associated with two VEGFR-2 inhibitors, in particular axitinib and lenvatinib, as well as investigate the involvement of endothelin-1 (ET-1) system in the development of RTKI-induced hypertension. Combining diverse in vitro, ex vivo and in vivo approaches, the purpose of this study was also the identification of sensitive approaches to readily detect cardiovascular risk of these novel targeted therapies in preclinical settings. As the incidence of hypertension seems to be correlated to the potency of these therapeutics against VEGFR-2, we first quantified the inhibitory activity of a spectrum of RTKIs on VEGFR-2 mediated responses. The five RTKIs targeting VEGFR-2 tested in this study (axitinib, linifanib, vatalanib, SU-14813 and lenvatinib) showed a potent inhibition of VEGF165a-stimulated nuclear factor of activated T-cell (NFAT) response with IC50 values in nanomolar range, with axitinib and lenvatinib showing highest relative potency for the receptor. These two RTKIs were then selected for the characterisation of their haemodynamic effects in conscious and freely moving rats. Both axitinib and lenvatinib caused a significant hypertensive response, which was associated with an increased vascular tone in hindquarters and mesenteric arteries. Additionally, given the onset time for hypertension in the animal model used (24-48 hours), this in vivo model has proven to be a sensitive and translational approach for the prediction and early detection of haemodynamic effects of these novel targeted anticancer therapies. Second, we investigated the role of dual ETA/ETB receptor blockade with bosentan and selective ETA receptor antagonism with sitaxentan in the prevention of axitinib- and lenvatinib-induced hypertension. In conscious and freely moving rats, sitaxentan completely prevented the hypertensive response to axitinib and lenvatinib. These findings established the contribution of ET-1 to RTKI-induced hypertension. In particular, our results have demonstrated that such increase in BP is purely regulated by ETA receptors. The simultaneous evaluation of the role of endothelin receptors antagonism in preventing the RTKI-mediated alterations of vascular tone in regional vascular beds showed that axitinib- and lenvatinib-induced increase of mesenteric vascular tone could be independent of their hypertensive effect, and it may be mainly mediated by ETB receptors. Third, ex vivo studies were used to investigate the effect of axitinib and lenvatinib on vascular reactivity and endothelial function, while also assessing the role of arterial stiffness in the haemodynamic responses associated with these agents. Experiments on isolated mouse aortic segments showed that the treatment with axitinib and lenvatinib was not associated with endothelial dysfunction, as reported by the unaltered endothelium-dependent relaxation in response to acetylcholine (ACh). Endothelium-independent relaxation in response to nitric oxide (NO) donor was not affected by both axitinib and lenvatinib, suggesting a preserved vascular smooth muscle cells (VSMCs) function. In addition, the rodent oscillatory set-up to study arterial compliance (ROTSAC) was used to investigate the effect of axitinib and lenvatinib on arterial stiffness; no evidence was found that these agents affect arterial compliance in the time period evaluated in this study. Finally, in vivo experiments were performed to assess cardiac functional and structural changes induced by axitinib and lenvatinib in a mouse model. Echocardiographic measurements and pressure-volume loops analysis revealed an impairment of systolic function in response to lenvatinib. The treatment with this RTKI was also associated with structural changes of the left ventricle (LV), including left ventricular wall thinning and cavity enlargement, suggestive of drug-induced dilated cardiomyopathy.